EFFECT OF OZONATION PROCESS ON PHYSICOCHEMICAL AND RHEOLOGICAL PROPERTIES OF κ-CARRAGEENAN - AJI PRASETYANINGRUM; BAKTI JOS; RATNAWATI RATNAWATI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
κ-Carrageenan is a sulfated galactan extracted from red algae (Rhodophyceae) which has many functions. However, nonfood applications of κ-carrageenan have been limited by its superior gelling and viscosity properties. The effect of ozonation on physicochemical and rheological properties of κ-carrageenan solution at different pH was investigated. κ-Carrageenan solution was prepared in the ratio of 1:100 (w/v) and was treated with dissolved ozone with concentration of 80±2 ppm. This ozonation was conducted at different times and pH. The viscosity of ozone-treated κ-carrageenan solution was analyzed using Brookfield viscometer and the sulfate content was determined using FT-IR spectra and barium chloride-gelatin method. The results show that the viscosity of ozone-treated κ-carrageenan decreases appreciably with time. The highest percentage reduction in viscosity occurs at pH 3, followed by pH 7 and 10. The FT-IR spectra reveals that the chemical structure of degraded κ-carrageenan, in term of sulfate content, is only slightly affected by the ozone treatment.